2020
DOI: 10.3390/ijms21197085
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of CXCR4 Antagonist CX807 in a Rat Model of Hemorrhagic Stroke

Abstract: Intracerebral hemorrhage (ICH) is a major cause of stroke, with high mortality and morbidity. There is no effective pharmacological therapy for ICH. Previous studies have indicated that CXCR4 antagonists reduced microglia activation, attenuated infiltration of T cells, and improved functional recovery in ischemic stroke animals. The interaction of CXCR4 antagonists and ICH has not been characterized. The purpose of this study is to examine the neuroprotective action of a novel CXCR4 antagonist CX807 against IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Several studies have supported the effectiveness of anti-inflammatory treatment in animal models of ICH [11,12]. We recently demonstrated that early post-treatment with a CXCR4 antagonist CX807 inhibited inflammation and improved behavioral function in experimental ICH rats [13]. These data suggest that anti-inflammatory therapy may reduce brain damage after ICH.…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…Several studies have supported the effectiveness of anti-inflammatory treatment in animal models of ICH [11,12]. We recently demonstrated that early post-treatment with a CXCR4 antagonist CX807 inhibited inflammation and improved behavioral function in experimental ICH rats [13]. These data suggest that anti-inflammatory therapy may reduce brain damage after ICH.…”
Section: Introductionmentioning
confidence: 65%
“…ICH promotes the migration of peripheral immune cells, such as CD4 + and CD8 + T cells, to the lesioned brain [28,29]. We previously reported the expression of cytotoxic T-cell markers in the ICH brain [13]. In addition, the peak infiltration of CD4 T cells was between days 3 and 4 after ischemic injury in the mice [30].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations